Fanon, o reconhecimento do negro e o novo humanismo: horizontes descoloniais da tecnologia - Queiroz, Ivo Pereira de (2013)
This thesis take as its reference the problematic and work that constitute the thought of Frantz Fanon about colonialism and decolonization. The reflexion is attentive to the epistemic dimensions that pervade the work of this author and its possibilities to an analyses of technology and technological education. This work intends, as a whole, to evaluate, in the discourses that weave the narrative of Fanon’s archives, the conditioners that subject black people in a subaltern order of subjectivation, which restrict their appropriation of science and technology, toward the configuration of new discourses and alternative social practices. Fanon’s observations are reported about the relationship of the Algerian people with knowledges, products and professionals of science and technology, during the war of liberation, which allow us to suggest that Fanon would have being one of the precursors of STS Studies - Science, Technology and Society Studies. The analyses of the categories of acknowledgment and the notion of new humanism proposed by Fanon are aligned to sustain six categories of the liberation philosophy and of the poiesis – production philosophy – in the view of a decolonized technological design. The evidences collected are confronted with codes that racially mark the technological education in Brazil, in detriment of black people. Finalize with brief considerations, suggesting new studies about the themes raised along the thesis.